Pentingnya Implementasi Sistem Meritokrasi Dalam Instansi Pemerintahan Indonesia - Agil Sabani; Naiya Aulia; Nisriinaa Mazaya P; Savina Niken M (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
There are various government agencies around us; perhaps this raises the question of why some agencies seem more efficient and effective than others. One of the main factors that influences the performance of an agency is the implementation of a meritocracy system, where civil society is promoted and given responsibility based on their abilities and achievements, not connections or seniority alone. In this article, we will discuss in depth the importance of implementing a meritocracy system in government agencies to increase work accountability, supervision, and bureaucratic reform. We will also provide examples of agencies that have successfully implemented a meritocracy system.